Impact of the Optimistic Perspective on the Intention to Create Social Enterprises: A Comparative Study Between Portugal and Spain - Margaça, Clara; Hernández-Sánchez, Brizeida Raquel; Cardella, Giuseppina Maria; Sánchez-García, José Carlos (Frontiers in Psychology, 2021)
Social entrepreneurship (SE) enables business consolidation, combined with the production of positive impact and improvements in society. Aligned with 2030 Agenda for the achievement of the United Nations Sustainable Development Goals, it is important to clarify the role of social entrepreneurs, as they are making visible the impact of their creative ideas in several areas, from civic engagement to the environment, health and learning. The main purpose of this study is to specify a model of social entrepreneurial intention (SEI) and explore it by country, based on the dimensions of the Theory of Planned Behavior and how these are mediated by spirituality and optimism. With a convenience sample of 1476 Portuguese and Spanish students, Structural Equation Modeling (SEM) was used. For a deeply understanding, variables within the model were compared by country using t-rest, and multivariate analysis was done by each one separately. The mean comparison between countries, demonstrated that there are differences only between perceived behavioral control (PBC), Spirituality, Optimism and SEI, with Portuguese students scoring the highest values, in all variables except Optimism. A mediation path was carried out, and Spirituality mediate a significant effect between the three TPB dimensions in Portuguese students, but not in students from Spain. Finally, after discussing the results, theoretical and practical contributions are analyzed, with regard to the field of SE in Portugal and Spain, and alternatives are pointed out for a more social and sustainable entrepreneurial future.